1999
DOI: 10.1073/pnas.96.14.8110
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell tumor necrosis factor α response to FimH-expressingEscherichia coliis mediated by the glycosylphosphatidylinositol-anchored molecule CD48

Abstract: Mast cells are well known for their harmful role in IgE-mediated hypersensitivity reactions, but their physiological role remains a mystery. Several recent studies have reported that mast cells play a critical role in innate immunity in mice by releasing tumor necrosis factor ␣ (TNF-␣) to recruit neutrophils to sites of enterobacterial infection. In some cases, the mast cell TNF-␣ response was triggered when these cells directly bound FimH on the surface of Escherichia coli. We have identified CD48, a glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
169
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 41 publications
4
169
0
1
Order By: Relevance
“…Other enzymes, such as proteases, are known to exert microbicidal effects through cytokine production (42)(43)(44). Our findings in this study imply that proteases may not be the primary antimicrobial component in mast cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other enzymes, such as proteases, are known to exert microbicidal effects through cytokine production (42)(43)(44). Our findings in this study imply that proteases may not be the primary antimicrobial component in mast cells.…”
Section: Discussionmentioning
confidence: 59%
“…For instance, mast cells sense the type 1 fimbriae of E. coli through surface-expressed CD48, resulting in release of the potent neutrophil chemoattractant TNF-a in a process that is pivotal for elimination of the bacteria (42). Additionally, mast cell tryptase b I reportedly plays a central role in the host defenses of the lung by recruiting neutrophils (43), and cecal ligation and puncture models demonstrated that mast cell chymase is essential for survival in cases of septic peritonitis (44).…”
Section: Discussionmentioning
confidence: 99%
“…In specific immunity, they respond to Ag via receptor-bound IgE to release multiple mediators including histamine, eicosanoids, and cytokines, which together contribute to immediate allergic reactions and inflammatory cell recruitment (1,2). In innate immunity, mast cells release TNF in response to direct interaction with bacterial adhesion molecules, and this cytokine induces neutrophil recruitment with subsequent bacterial clearance through phagocytosis (3)(4)(5). A key element of phagocytosis and killing of bacteria, and possibly of importance also in mediating and regulating inflammation, is the production of reactive oxygen species (ROS) 3 (6 -8).…”
mentioning
confidence: 99%
“…NADPH oxidase of phagocytic cells can also be activated by protein kinase C agonists such as PMA (12). Because mast cells are pivotal to neutrophil-mediated defense against certain bacteria (3)(4)(5) and both neutrophils and macrophages phagocytose and kill bacteria by ROS production (9 -11), the possible contribution of mast cells themselves to ROS production is an important issue. Although mucosal mast cells can phagocytose and kill bacteria, evidently via generation of ROS (13), the question of whether mast cell ROS generation accompanies degranulation is less clear cut.…”
mentioning
confidence: 99%
“…It was recently shown that mouse mast cells bind various enteric bacteria by specifically recognizing a 29-kDa mannose-binding lectin, FimH [3], presented on the tips of hair-like appendages of the bacteria [35]. The identity of the FimH binding moiety on the rodent mast cell membrane was recently shown to be CD48, a GPI-linked moiety of the immunoglobulin superfamily [36]. This study attempted to identify the ligand in the bacteria responsible for binding of human mast cells.…”
Section: Discussionmentioning
confidence: 99%